2010
DOI: 10.1177/1541204010366619
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Importation and Deprivation Factors on Violent Misconduct: An Examination of Black and Latino Youth in Prison

Abstract: There are volumes of research on inmate misconduct; however, few studies focus on institutional violence among juvenile inmates and even fewer examine violent misconduct among youth sentenced as adults and transferred to prison. The current study draws on theories of importation and deprivation and relies on self-report data from in-depth interviews conducted between February 2001 and March 2003 with 95 male juvenile inmates incarcerated in adult prisons in Arizona and New York. The current study fills a void … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 29 publications
3
75
0
1
Order By: Relevance
“…Inmate disturbances and institutional disorder increase with the concentration of gangs in correctional facilities (Useem and Reisig, 1999). Inmates who affiliate with gangs are responsible for a disproportionately large portion of institutional misconduct, particularly violence (Griffin and Hepburn, 2006;Huebner, 2003;Shelden, 1991;Tasca, Griffin, and Rodriguez, 2010). Gangs also present less apparent challenges to the management of facilities, such as the administration of programming and inmate housing arrangements complicated by intergang rivalries (Crouch and Marquart, 1989;DiIulio, 1990;Mears, 2005;Toch, 2007;Trulson, Marquart, and Kawucha, 2006).…”
mentioning
confidence: 99%
“…Inmate disturbances and institutional disorder increase with the concentration of gangs in correctional facilities (Useem and Reisig, 1999). Inmates who affiliate with gangs are responsible for a disproportionately large portion of institutional misconduct, particularly violence (Griffin and Hepburn, 2006;Huebner, 2003;Shelden, 1991;Tasca, Griffin, and Rodriguez, 2010). Gangs also present less apparent challenges to the management of facilities, such as the administration of programming and inmate housing arrangements complicated by intergang rivalries (Crouch and Marquart, 1989;DiIulio, 1990;Mears, 2005;Toch, 2007;Trulson, Marquart, and Kawucha, 2006).…”
mentioning
confidence: 99%
“…However, it should be noted that for the majority of these studies, the samples consisted of either predominately or only male offenders. Male gender (Kuanliang & Sorensen, 2008), antisocial attitudes (Arbach-Lucioni, Martinez-García, & Andrés-Pueyo, 2012), antisocial behaviour (Gendreau, Goggin & Law, 1997), mental health issues (Kuanliang & Sorensen, 2008), substance use/abuse problems (Arbach-Lucioni et al, 2012), and gang membership (Tasca, Griffin & Rodriguez, 2010) have also been found to contribute to institutional misconducts.…”
Section: Predictors Of Institutional Misconduct In Offendersmentioning
confidence: 99%
“…Numerous studies have examined sex differences in factors, such as age, contributing to prison misconduct (Berg & DeLisi, 2006;Camp et al, 2003;Craddock 1996;Gover, Pérez, & Jennings, 2008;Jiang & Winfree, 2006;McClellan, 1994); however, most studies focus on male only samples (Cunningham & Sorensen, 2007;DeLisi et al, 2011;Harer & Steffensmeier, 1996;Kuanliang, Sorensen, & Cunningham, 2008;McReynolds & Wasserman, 2008;McShane & Williams, 1989;Morris et al, 2010;Steiner & Wooldredge, 2008;Tasca, Griffin, & Rodriguez, 2010) and a small number examine female only samples (Blackburn & Trulson, 2010;Houser, Belenko, & Brennan, 2012;Pollock, Mullings, & Crouch, 2006;Steiner & Wooldredge, 2009b). Much less empirical attention has been paid to the sex differences in prison misconduct and especially the conditioning effect sex may have on the age-misconduct relationship.…”
Section: Age Sex and Prison Misconductmentioning
confidence: 99%